Correlation between calibrated computerized tomographic findings and histopathologic grade/stage in non-alcoholic steatohepatitis - Ataseven, H; Yildirim, MH; Yalniz, M; Bahcecioglu, IH; Ozercan, IH; Celebi, S; Demir, A (Elsevier Science Bv, 2003)
[Abstract Not Available]
38th Annual Meeting of the European-Association-for-the-Study-of-the-Liver -- MAR 29-APR 01, 2003 -- ISTANBUL, TURKEY